1997
DOI: 10.1002/(sici)1520-6394(1997)5:1<29::aid-da5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of ketamine in the holeboard, the elevated-plus maze, and the social interaction test in Wistar rats

Abstract: Although noncompetitive NMDA receptor antagonists have shown an anxiolyticlike profile in several studies, such effects have not been observed consistently. Previous studies with ketamine, a noncompetitive NMDA antagonist, have employed only shock tests of anxiety based on conflict procedures. In the present experiment, the effect of an acute low dose of ketamine (7 mg/kg) was examined in adult male Wistar rats tested in three nonconflict tests: holeboard, social interaction, and elevated plus‐maze paradigms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 21 publications
4
29
0
Order By: Relevance
“…Clinical studies have shown that acute administration of ketamine (as well as other NMDA antagonists) ameliorates depressive symptoms in major depressed patients (Zarate et al 2006;Berman et al 2000). In line with these findings, ketamine induces anxiolytic-and antidepressant-like effects in rodent models of anxiety and depression (Kos et al 2006;Yilmaz et al 2002;Silvestre et al 1997), an effect also associated with an increase in BDNF in the hippocampus (Garcia et al 2008). Thus, it is possible that the described antidepressant action of ketamine in humans can be mediated by BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that acute administration of ketamine (as well as other NMDA antagonists) ameliorates depressive symptoms in major depressed patients (Zarate et al 2006;Berman et al 2000). In line with these findings, ketamine induces anxiolytic-and antidepressant-like effects in rodent models of anxiety and depression (Kos et al 2006;Yilmaz et al 2002;Silvestre et al 1997), an effect also associated with an increase in BDNF in the hippocampus (Garcia et al 2008). Thus, it is possible that the described antidepressant action of ketamine in humans can be mediated by BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, acute and subchronic treatment of MK-801 (0.1–0.3 mg/kg) has been shown to reduce social interaction in adult male rats and mice (de Moura Linck et al, 2008; Matsuoka et al, 2008; Rung et al, 2005). Further, acute and subchronic administration of ketamine (7–30 mg/kg) impaired social interaction in adult male rats (Becker et al, 2003; Silvestre et al, 1997; Uribe et al, 2013). The deficits in social interaction observed in rodents following PCP and other NMDA receptor antagonists seem to correlate to the PCP- and ketamine-induced social withdrawal seen in humans, further supporting social interaction as readout for investigating negative symptoms associated with schizophrenia, more specifically asociality (Sams-Dodd, 1995b).…”
Section: Social Interactionmentioning
confidence: 99%
“…Studies by Silvestre et al (1997) and Koros et al (2007), using acute (7 mg/kg) and subchronic (2-16 mg/kg for 3 days) administration regimens, respectively, reported that ketamine treatment produced a significant decrease in social interaction time in pairs of rats. In contrast other studies have found that subchronic treatment (30 mg/kg for 5 days) had no effect on social interaction time, but significantly reduced nonaggressive behaviour (e.g.…”
Section: Nmda Receptor Antagonists (Tables 2-4)mentioning
confidence: 99%